A test method and application of battery manganese dissolution
Through the cleaning and digestion determination of manganese positive electrode material, the problem of low manganese dissolution test results was solved, and a more accurate and reliable evaluation of manganese dissolution was achieved, ensuring the stability and credibility of the test.
Patent Information
- Application Number
- CN202211080867.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-05
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-09-05
AI Technical Summary
In the prior art, the manganese positive electrode material battery lacks a unified standard for the manganese dissolution amount test method during recycling, resulting in a low measurement result and cannot accurately reflect the actual manganese dissolution amount.
The positive electrode material obtained by cleaning and separating the active components, and measuring the change in manganese content through digestion to judge the manganese dissolution amount, and ultrasonic heating and dilution capacity-controlled methods ensure the stability and credibility of the test results.
Accurate measurement of the manganese dissolution amount is achieved, the problem of low measurement results is avoided, the stability and credibility of the test are improved, and the actual manganese dissolution can be better reflected.
Smart Images

Figure BDA0003833182120000131 
Figure BDA0003833182120000132 
Figure BDA0003833182120000141
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a test method and application of manganese dissolution in batteries. Background Art
[0002] Lithium manganese iron phosphate has a regular olivine structure, and has the same advantages as lithium iron phosphate, such as low cost, high safety performance, high thermal stability, no spontaneous combustion when punctured or overcharged, long life, safety and no explosion risk, etc. It also makes up for the shortcoming of low energy density of lithium iron phosphate. However, during the recycling process of lithium manganese iron phosphate or lithium manganese oxide batteries, manganese is dissolved due to the Jahn-Teller effect. The dissolved manganese can not only react with the electrolyte, but also deposit on the surface of the negative electrode, destroying the SEI film and causing increased battery polarization.
[0003] At present, there is no unified standard for the test method of manganese content dissolved during the recycling process of manganese positive electrode material batteries. CN105514422A discloses placing a fully charged battery in a 60°C oven for high temperature storage for 7 days, disassembling the lithium negative electrode sheet of the battery, dissolving it with a 0.1 mol / L HCl aqueous solution, and testing the amount of manganese ions in the HCl solution by AAS, which is the amount of manganese dissolved. This method ignores the fact that part of the manganese dissolved from the positive electrode material reacts with the electrolyte, resulting in a lower amount of manganese dissolved than the actual amount.
[0004] Therefore, how to provide a method for testing the manganese dissolution content in manganese positive electrode materials to avoid the obtained manganese dissolution amount being lower than the actual amount, while at the same time having a high stability of the test results, is a problem that urgently needs to be solved. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a test method and application of manganese dissolution in a battery. The present invention cleans the disassembled positive electrode material, separates the active components and digests them, thereby directly measuring the change in the manganese content in the positive electrode material to obtain the manganese dissolution amount. The invention is simple to operate, can directly measure the change in the manganese content in the positive electrode material as a judgment of the manganese dissolution amount, and has good stability; and this method can better reflect the actual manganese dissolution amount and has a high degree of credibility.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for testing the dissolution of manganese in a battery, the method comprising the following steps:
[0008] (1) Taking the battery before and after the cycle, disassembling them respectively to prepare the test solution, specifically comprising the following steps:
[0009] (a) disassembling a battery to obtain a positive electrode sheet, and then cleaning and separating the positive electrode sheet to obtain a positive electrode material, wherein the positive electrode material includes an active component;
[0010] (b) digesting the cathode material, diluting the digestion solution to obtain a solution to be tested;
[0011] Wherein, when the battery is a battery before cycling, the prepared solution to be tested is the first solution to be tested; when the battery is a battery after cycling, the prepared solution to be tested is the second solution to be tested;
[0012] (2) The content of manganese in the first solution to be tested is recorded as a, the content of manganese in the second solution to be tested is recorded as b, and the amount of manganese dissolved in the battery is recorded as ((ab) / a)×100%.
[0013] The present invention disassembles the whole battery to obtain a manganese-containing positive electrode sheet, and then cleans and removes the manganese and electrolyte dissolved on the surface of the positive electrode sheet to prevent errors in the test results of the manganese content. Then, the current collector in the positive electrode sheet, such as aluminum foil, is separated, and finally the positive electrode material in the positive electrode sheet is left for digestion and dilution. Through digestion, the manganese-containing component in the active component can be completely decomposed, and then converted into an ionic state and exist in the solution to be tested. The manganese content in the solution to be tested can be determined by testing means. By comparing the manganese content of the active component in the positive electrode sheet before the cycle and the manganese content of the active component in the positive electrode sheet after the cycle, the change in manganese content during the use of the battery, that is, the amount of manganese dissolved, can be obtained. The operation is simple, the stability is good, and it has a high degree of credibility.
[0014] In the present invention, if the manganese dissolved on the surface of the positive electrode sheet and the electrolyte are not removed by washing, the dissolved manganese attached to the surface of the positive electrode sheet and the dissolved manganese contained in the electrolyte attached to the surface of the positive electrode sheet will enter the solution to be tested, resulting in a low amount of manganese dissolved and poor credibility. If the amount of manganese dissolved is tested by digesting the negative electrode sheet, the dissolved manganese attached to the surface of the positive electrode material and the manganese remaining in the electrolyte will be ignored, resulting in a measured amount of manganese dissolved that is lower than the actual amount and poor credibility.
[0015] Preferably, the method for separation after cleaning in step (1) is: washing the positive electrode sheet in a detergent, and then scraping the positive electrode material off the surface of the current collector after drying.
[0016] In the present invention, the positive electrode sheet is placed in a detergent for washing, and the manganese and electrolyte dissolved on the surface thereof will dissolve in the detergent. It should be noted that the positive electrode material includes a binder and an optional conductive agent in addition to the active component, but their presence will not affect the test results, so the binder and conductive agent present in the positive electrode sheet are not specially treated. After the washed positive electrode sheet is dried, the positive electrode material can be scraped off the surface of the current collector. The process is simple, easy to operate, efficient, and reduces costs.
[0017] Preferably, the cleaning detergent is at least one of water, anhydrous ethanol and ethanol-water solution.
[0018] In the present invention, the detergent can effectively remove manganese and electrolyte on the surface of the positive electrode, and is non-toxic, non-polluting, and environmentally friendly. If alkaline solution is used as a detergent, manganese in the active component may be dissolved again, and the current collector such as aluminum foil will also dissolve in the alkaline solution and cannot be recovered, which increases the cost.
[0019] Preferably, the concentration of ethanol in the ethanol aqueous solution is 40-75%, for example, 40%, 45%, 50%, 55%, 60%, 65%, 70% or 75%, etc.
[0020] In the present invention, if the concentration of ethanol in the ethanol aqueous solution is too high, the cleaning cost will increase, while if it is too low, the electrolyte or other organic components may not be completely cleaned.
[0021] Preferably, the washing method includes at least one of stirring, ultrasound and solvent washing, preferably ultrasound, the frequency of the ultrasound is preferably 20-40KHz, such as 20KHz, 25KHz, 30KHz, 35KHz or 40KHz, etc., and the number of ultrasounds is 1-3 times, such as 1 time, 2 times or 3 times, etc.
[0022] In the present invention, the ultrasonic treatment can efficiently remove the residual dissolved manganese attached to the positive electrode material and the electrolyte attached to the surface, and can promote the stripping of the positive electrode material and the current collector.
[0023] Preferably, the stirring and / or ultrasonic process is accompanied by heating, and the heating temperature is preferably 40-60°C, for example, 40°C, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C, 58°C or 60°C, etc.
[0024] Preferably, the solvent used in the solvent washing process is a solvent at a certain temperature, and the certain temperature is greater than room temperature, preferably 40-60°C, for example 40°C, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C, 58°C or 60°C, etc.
[0025] In the present invention, room temperature refers to 25±5°C. When heating treatment is performed, the rate of washing away the dissolved manganese in the electrolyte and the particle surface can be increased, and the use of heating ultrasound can combine the advantages of ultrasound and heating treatment, which can prevent the heating and stirring time from being too long, which may cause further dissolution of manganese in the crystal structure.
[0026] In the present invention, if the heating temperature is too low, the removal rate of manganese dissolved from the surface and electrolyte adhered to the surface will be slowed down, and the efficiency will be reduced, while if the heating temperature is too high, manganese in the crystal structure will be dissolved.
[0027] Preferably, the washing time is 8-12 min, for example, 8 min, 9 min, 10 min, 11 min or 12 min, etc.
[0028] In the present invention, if the washing time is too long, the manganese in the crystal structure will be further dissolved, while if the washing time is too short, the washing will be insufficient, affecting the accuracy of the result.
[0029] Preferably, the drying temperature is 80-130°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C 105°C, 110°C, 115°C, 120°C, 125°C or 130°C, etc.
[0030] In the present invention, if the drying temperature is too low, the separation rate between the positive electrode material and the current collector is low; and if the temperature is too high, the active substance of the positive electrode material will be oxidized.
[0031] Preferably, the drying time is 5-10 h, for example, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h.
[0032] Preferably, the digestion in step (2) comprises at least one of wet digestion, dry digestion and microwave digestion, preferably wet digestion;
[0033] In the present invention, the wet digestion has a fast decomposition speed, a short processing time, and less element loss. It should be noted that nitric acid should be added in time to avoid carbonization. If carbonization occurs, it must be cooled immediately and then nitric acid is added.
[0034] Preferably, the digestion agent in the wet digestion is an acidic compound, including at least one of hydrochloric acid, nitric acid, perchloric acid and aqua regia, preferably hydrochloric acid and / or nitric acid.
[0035] In the present invention, the acid used for digestion will dissolve the active components in the positive electrode material, but will not dissolve the binder and the conductive agent.
[0036] Preferably, the digestion agent concentration for digestion in step (2) is 0.1-10mol / L, for example 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1mol / L, 1.5mol / L, 2mol / L, 2.5mol / L, 3mol / L, 3.5mol / L, 4mol / L, 4.5mol / L, 5mol / L, 5.5mol / L, 6mol / L, 6.5mol / L, 7mol / L, 7.5mol / L, 8mol / L, 8.5mol / L, 9mol / L, 9.5mol / L or 10mol / L, etc., preferably 0.4-1mol / L.
[0037] In the present invention, if the concentration of the acid used for digestion is too low, the active components may not be completely dissolved, while if the concentration of the acid is too high, there may be danger.
[0038] Preferably, the amount of digester used in the digestion in step (2) is 20-50 mL / 1 g of positive electrode material, that is, 20 mL, 30 mL, 40 mL or 50 mL of digester is added for every 1 g of positive electrode material sample.
[0039] Preferably, the digestion time in step (2) is 20-40 min, for example, 20 min, 25 min, 30 min, 35 min or 40 min.
[0040] Preferably, the digestion temperature in step (2) is 60-300°C, for example 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C or 300°C, etc., preferably 80-120°C.
[0041] Preferably, the method for diluting and fixing the volume of the digestion solution in step (2) is: transferring the digestion solution to a volumetric flask with a volume of V, adding water to fix the volume, and then taking out a volume of V from the volumetric flask. 0 Transfer the solution to another volumetric flask with a volume of V, add acid, and then make up to volume with water to obtain the solution to be tested.
[0042] In the present invention, the volume of the volumetric flask is not limited, as long as the concentration of the solution to be tested after dilution and volume adjustment is within the test range of the instrument.
[0043] Preferably, the volume is V 0 The volume ratio of the solution to the acid is 1:(8-12), for example 1:8, 1:9, 1:10, 1:11 or 1:12, etc.
[0044] Preferably, the acid used for dilution and volume determination in step (2) comprises at least one of hydrochloric acid, nitric acid, perchloric acid and aqua regia.
[0045] Preferably, the positive electrode sheet in step (1) comprises a manganese-containing positive electrode active component, and the manganese-containing positive electrode active component comprises LiMn x Fe 1-x PO 4 , 0<x≤1, for example, x is 0.2, 0.4, 0.6, 0.8 or 1, etc.
[0046] Preferably, the current collector comprises at least one of aluminum foil and nickel foil, preferably aluminum foil.
[0047] Preferably, in step (3), the testing methods for the content of manganese in the first test solution and the second test solution independently include at least one of ICP-OES, ICP-AES and ICP-MS.
[0048] As a preferred technical solution, the testing method comprises the following steps:
[0049] (1) Taking the battery before and after the cycle, disassembling them respectively to prepare the test solution, specifically comprising the following steps:
[0050] (a) disassembling the battery to obtain a positive electrode sheet, placing the positive electrode sheet in a detergent and ultrasonicating the positive electrode sheet at 40-60° C. for 8-12 min, for 1-3 times in total, with a frequency of 20-40 KHz, and replacing the detergent each time the ultrasonication is performed, and then drying the positive electrode sheet at 80-130° C. for 5-10 h. After drying, scraping the positive electrode material off the surface of the current collector to obtain the positive electrode material;
[0051] (b) taking the positive electrode material and placing it in 0.1-10 mol / L acidic compound for digestion, the amount of the digester is 20-50 mL / 1 g of positive electrode material, the digestion temperature is 60-300° C., the digestion time is 20-40 min, the solid-liquid separation is performed, and the filtrate is taken as the digestion solution, and then the digestion solution is diluted twice to obtain a solution to be tested;
[0052] Wherein, when the battery is a battery before cycling, the prepared solution to be tested is the first solution to be tested; when the battery is a battery after cycling, the prepared solution to be tested is the second solution to be tested;
[0053] (2) The content of manganese in the first solution to be tested is recorded as a, the content of manganese in the second solution to be tested is recorded as b, and the amount of manganese dissolved in the battery is recorded as ((ab) / a)×100%.
[0054] In a second aspect, the present invention provides a method for testing manganese dissolution in a battery, wherein the method is used in the field of lithium-ion batteries.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] The present invention cleans the disassembled positive electrode material, separates the active components and digests them, thereby directly measuring the change in the manganese content in the positive electrode material to obtain the manganese dissolution amount. The invention is simple to operate, can directly measure the change in the manganese content in the positive electrode material as a judgment of the manganese dissolution amount, and has good stability; and the method can better reflect the actual manganese dissolution amount and has a high degree of credibility. DETAILED DESCRIPTION
[0057] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0058] Example 1
[0059] This embodiment provides a method for testing the dissolution of manganese in a battery, and the method comprises the following steps:
[0060] (1) Taking the battery before and after the cycle, disassembling them respectively to prepare the test solution, specifically comprising the following steps:
[0061] (a) Disassemble the battery to obtain LiMn 0.2 Fe 0.8 PO 4 Positive electrode sheet: put the positive electrode sheet into 100 mL of anhydrous ethanol and ultrasonicate at 60°C for 10 min, twice at a frequency of 30 KHz, and replace the detergent each time, then dry at 130°C for 8 h, and after drying, scrape the positive electrode material off the surface of the aluminum foil to obtain the positive electrode material;
[0062] (b) Take 2g of positive electrode material and place it in 95mL of 1mol / L hydrochloric acid for digestion at 100℃ for 30min. Filter the digestion solution and transfer it to a 250mL volumetric flask. Add deionized water to the mark and shake well. Take the solution in the 1mL volumetric flask to another 250mL volumetric flask, add 10mL of 1mol / L hydrochloric acid, dilute to the mark with deionized water, and shake well to obtain the solution to be tested.
[0063] Wherein, when the battery is a battery before cycling, the prepared solution to be tested is the first solution to be tested; when the battery is a battery after cycling, the prepared solution to be tested is the second solution to be tested;
[0064] (2) using ICP-OES method to obtain the content a of manganese in the first solution to be tested and the content b of manganese in the second solution to be tested;
[0065] (3) The amount of manganese eluted from the battery is measured and recorded as ((ab) / a)×100%.
[0066] Example 2
[0067] This embodiment provides a method for testing the dissolution of manganese in a battery, and the method comprises the following steps:
[0068] (1) Taking the battery before and after the cycle, disassembling them respectively to prepare the test solution, specifically comprising the following steps:
[0069] (a) Disassemble the battery to obtain LiMn0.4 Fe 0.6 PO 4 Positive electrode sheet: put the positive electrode sheet into 90 mL of water and ultrasonicate at 50°C for 8 min, for a total of 3 times, with a frequency of 20 KHz, and replace the detergent every time of ultrasonication, and then dry at 100°C for 5 h. After drying, scrape the positive electrode material from the surface of the aluminum foil to obtain the positive electrode material;
[0070] (b) Take 2g of positive electrode material and digest it in 90mL of 5mol / L perchloric acid at 60℃ for 20min. Filter the digestion solution and transfer it to a 250mL volumetric flask. Add deionized water to the mark and shake well. Take 1mL of the solution in the volumetric flask to another 250mL volumetric flask, add 8mL of 5mol / L perchloric acid, dilute to the mark with deionized water and shake well to obtain the solution to be tested.
[0071] Wherein, when the battery is a battery before cycling, the prepared solution to be tested is the first solution to be tested; when the battery is a battery after cycling, the prepared solution to be tested is the second solution to be tested;
[0072] (2) using ICP-AES to obtain the manganese content a in the first solution to be tested and the manganese content b in the second solution to be tested;
[0073] (3) The amount of manganese eluted from the battery is measured and recorded as ((ab) / a)×100%.
[0074] Example 3
[0075] This embodiment provides a method for testing the dissolution of manganese in a battery, and the method comprises the following steps:
[0076] (1) Taking the battery before and after the cycle, disassembling them respectively to prepare the test solution, specifically comprising the following steps:
[0077] (a) Disassemble the battery to obtain LiMn 0.6 Fe 0.4 PO 4 Positive electrode sheet: put the positive electrode sheet into 200 mL of ethanol aqueous solution, wherein the molar ratio of ethanol to water is 50%, and ultrasonicate at 40°C for 12 min, once in total, with a frequency of 40 KHz, and replace the detergent every time of ultrasonication, and then dry at 80°C for 10 h. After drying, scrape the positive electrode material from the surface of the aluminum foil to obtain the positive electrode material;
[0078] (b) Take 2g of positive electrode material and digest it in 80mL of 8mol / L aqua regia at 300℃ for 40min. Filter the digestion solution and transfer it to a 250mL volumetric flask. Add deionized water to the mark and shake well. Take 1mL of the solution in the volumetric flask to another 250mL volumetric flask, add 10mL of 8mol / L aqua regia, dilute to the mark with deionized water and shake well to obtain the solution to be tested.
[0079] Wherein, when the battery is a battery before cycling, the prepared solution to be tested is the first solution to be tested; when the battery is a battery after cycling, the prepared solution to be tested is the second solution to be tested;
[0080] (2) using ICP-MS to obtain the manganese content a in the first solution to be tested and the manganese content b in the second solution to be tested;
[0081] (3) The amount of manganese eluted from the battery is measured and recorded as ((ab) / a)×100%.
[0082] Example 4
[0083] This embodiment provides a method for testing the dissolution of manganese in a battery, and the method comprises the following steps:
[0084] (1) Taking the battery before and after the cycle, disassembling them respectively to prepare the test solution, specifically comprising the following steps:
[0085] (a) Disassemble the battery to obtain LiMn 0.8 Fe 0.2 PO 4 Positive electrode sheet: put the positive electrode sheet into 200 mL of ethanol aqueous solution, wherein the molar ratio of ethanol to water is 60%, and ultrasonicate at 50°C for 10 min, twice in total, with a frequency of 25 KHz, and replace the detergent every time of ultrasonication, and then dry at 80°C for 9 h. After drying, scrape the positive electrode material from the surface of the aluminum foil to obtain the positive electrode material;
[0086] (b) Take 2g of positive electrode material and digest it in 50mL of 2mol / L aqua regia at 200℃ for 30min. Filter the digestion solution and transfer it to a 250mL volumetric flask. Add deionized water to the mark and shake well. Take 1mL of the solution in the volumetric flask to another 250mL volumetric flask, add 12mL of 2mol / L aqua regia, dilute to the mark with deionized water and shake well to obtain the solution to be tested.
[0087] Wherein, when the battery is a battery before cycling, the prepared solution to be tested is the first solution to be tested; when the battery is a battery after cycling, the prepared solution to be tested is the second solution to be tested;
[0088] (2) using ICP-OES method to obtain the content a of manganese in the first solution to be tested and the content b of manganese in the second solution to be tested;
[0089] (3) The amount of manganese eluted from the battery is measured and recorded as ((ab) / a)×100%.
[0090] Example 5
[0091] This embodiment provides a method for testing the dissolution of manganese in a battery, and the method comprises the following steps:
[0092] (1) Taking the battery before and after the cycle, disassembling them respectively to prepare the test solution, specifically comprising the following steps:
[0093] (a) Disassemble the battery to obtain LiMnPO 4 Positive electrode sheet: put the positive electrode sheet into 200 mL of ethanol aqueous solution, wherein the molar ratio of ethanol to water is 55%, and ultrasonicate at 45°C for 10 min, twice at a frequency of 35 KHz, and replace the detergent every time of ultrasonication, and then dry at 120°C for 6 h. After drying, scrape the positive electrode material from the surface of the aluminum foil to obtain the positive electrode material;
[0094] (b) Take 2g of positive electrode material and place it in 40mL of 0.4mol / L nitric acid for digestion at 250℃ for 25min. Filter the digestion solution, transfer the digestion solution to a 250mL volumetric flask, add deionized water to the mark, and shake well. Take 1mL of the solution in the volumetric flask to another 250mL volumetric flask, add 10mL of 0.4mol / L nitric acid, dilute to the mark with deionized water, and shake well to obtain the solution to be tested;
[0095] Wherein, when the battery is a battery before cycling, the prepared solution to be tested is the first solution to be tested; when the battery is a battery after cycling, the prepared solution to be tested is the second solution to be tested;
[0096] (2) using ICP-OES method to obtain the content a of manganese in the first solution to be tested and the content b of manganese in the second solution to be tested;
[0097] (3) The amount of manganese eluted from the battery is measured and recorded as ((ab) / a)×100%.
[0098] Example 6
[0099] The difference between this embodiment and embodiment 1 is that in step (1), 100 mL of anhydrous ethanol is used to rinse the positive electrode sheet.
[0100] The rest of the preparation methods and parameters were the same as those in Example 1.
[0101] Example 7
[0102] The difference between this embodiment and embodiment 1 is that in step (1), the positive electrode sheet is washed by stirring, the stirring paddle speed is 10 r / min, and the solvent is 100 mL of anhydrous ethanol.
[0103] The rest of the preparation methods and parameters were the same as those in Example 1.
[0104] Example 8
[0105] The difference between this embodiment and embodiment 1 is that the temperature of ultrasound in step (1) is 25°C.
[0106] The rest of the preparation methods and parameters were the same as those in Example 1.
[0107] Example 9
[0108] The difference between this embodiment and embodiment 1 is that the temperature of ultrasound in step (1) is 100°C.
[0109] The rest of the preparation methods and parameters were the same as those in Example 1.
[0110] Example 10
[0111] The difference between this embodiment and embodiment 1 is that the ultrasonication time in step (1) is 4 minutes.
[0112] The rest of the preparation methods and parameters were the same as those in Example 1.
[0113] Embodiment 11
[0114] The difference between this embodiment and embodiment 1 is that the ultrasonication time in step (1) is 16 minutes.
[0115] The rest of the preparation methods and parameters were the same as those in Example 1.
[0116] Comparative Example 1
[0117] The difference between this comparative example and Example 1 is that the disassembled LiMn 0.2 Fe 0.8 PO 4 The positive electrode sheet was dried directly at 130°C for 8 h without being cleaned, and the positive electrode material layer was scraped off the surface of the aluminum foil after drying.
[0118] The rest of the preparation methods and parameters were the same as those in Example 1.
[0119] Comparative Example 2
[0120] (1) The negative electrode sheet obtained by disassembling the battery in Example 1 was dried at 130° C. for 8 h, and the negative electrode material was separated from the copper foil after drying;
[0121] (2) All negative electrode materials were placed in 95 mL of 1 mol / L hydrochloric acid and digested at 100°C for 30 min. The solution was transferred to a 250 mL volumetric flask, 10 mL of 1 mol / L hydrochloric acid was added, and the volume was adjusted to the mark with deionized water. The solution was shaken to obtain the test solution.
[0122] (3) ICP-OES was used to determine the manganese content in the test solution.
[0123] (4) The amount of manganese dissolved in the battery is obtained from formula I:
[0124]
[0125] Among them, ρ 负 is the mass concentration of Mn element, in μg / mL; V 4 is the volume of the fixed volume, in mL; m 0 It is the mass of Mn, the active component of the positive electrode, in the battery before cycling, in g.
[0126] Comparative Example 3
[0127] The difference between this comparative example and Example 3 is that the disassembled LiMn 0.6 Fe 0.4 PO 4 The positive electrode sheet was dried directly at 80°C for 10 h without being cleaned, and the positive electrode material layer was scraped off the surface of the aluminum foil after drying.
[0128] The rest of the preparation methods and parameters were the same as those in Example 3.
[0129] Comparative Example 4
[0130] (1) The negative electrode sheet obtained by disassembling the battery in Example 3 was dried at 80° C. for 10 h, and the negative electrode material layer was separated from the copper foil after drying;
[0131] (2) All negative electrode material layers were placed in 80 mL of 8 mol / L aqua regia and immersed at 300 °C for 40 min. The solution was transferred to a 250 mL volumetric flask, 10 mL of 8 mol / L aqua regia was added, and the volume was adjusted to the mark with deionized water. The solution was shaken to obtain the test solution.
[0132] (3) ICP-OES was used to determine the manganese content in the test solution.
[0133] (4) The amount of manganese dissolved in the battery is obtained from formula I:
[0134]
[0135] Among them, ρ 负 is the mass concentration of Mn element, in μg / mL; V 4 is the volume of the fixed volume, in mL; m0 It is the mass of Mn, the active component of the positive electrode, in the battery before cycling, in g.
[0136] Comparative Example 5
[0137] The difference between this comparative example and Example 5 is that the disassembled LiMnPO 4 The positive electrode sheet was dried directly at 120°C for 6 h without being cleaned, and the positive electrode material layer was scraped off the surface of the aluminum foil after drying.
[0138] The rest of the preparation methods and parameters were the same as those in Example 5.
[0139] Comparative Example 6
[0140] (1) The negative electrode sheet obtained by disassembling the battery in Example 5 was dried at 120° C. for 6 h, and the negative electrode material layer was separated from the copper foil after drying;
[0141] (2) All negative electrode material layers were placed in 40 mL of 0.4 mol / L nitric acid and immersed at 250°C for 25 min. The solution was transferred to a 250 mL volumetric flask, 10 mL of 0.4 mol / L nitric acid was added, and the volume was adjusted to the mark with deionized water. The solution was shaken to obtain the test solution.
[0142] (3) ICP-OES was used to determine the manganese content in the test solution.
[0143] (4) The amount of manganese dissolved in the battery is obtained from formula I:
[0144]
[0145] Among them, ρ 负 is the mass concentration of Mn element, in μg / mL; V 4 is the volume of the fixed volume, in mL; m 0 It is the mass of Mn, the active component of the positive electrode, in the battery before cycling, in g.
[0146] The manganese contents obtained by the test methods provided in Examples 1-11 and Comparative Examples 1-6 were statistically analyzed, and the results are shown in Table 1.
[0147] Table 1
[0148]
[0149]
[0150] analyze:
[0151] Comparison of the data results of Example 1 with those of Examples 6 and 7 shows that ultrasonic heating, rinsing, and stirring are used to remove the dissolved manganese and electrolyte attached to the surface of the positive electrode material. Ultrasonic heating is the most thorough method, and the manganese dissolution amount is measured to be 0.0269%. At the same time, ultrasonic heating cleaning can also promote the separation of the positive electrode material layer and the current collector, which greatly facilitates the subsequent processes.
[0152] By comparing the data results of Example 1 with those of Examples 8 and 9, it can be seen that when the positive electrode sheet is cleaned by ultrasonic heating, when the temperature is too low, the removal rate of manganese dissolved from the surface of the positive electrode material and the electrolyte adhering to the surface is slowed down, and the measured manganese dissolution amount is low; when the temperature is too high, the manganese in the crystal structure is further dissolved, and the measured manganese dissolution amount is large.
[0153] By comparing the data results of Example 1 with those of Examples 10 and 11, it can be seen that when the positive electrode is cleaned by ultrasonic heating, the ultrasonic cleaning time is too short, the cleaning is insufficient, and the test result is low; while the ultrasonic cleaning time is too long, the manganese in the crystal structure is further dissolved, and the test result is high.
[0154] By comparing the data results of Example 1 with Comparative Example 1, Example 3 with Comparative Example 3, and Example 5 with Comparative Example 5, it can be seen that the manganese dissolution test results obtained by directly drying the positive electrode sheet without cleaning are smaller than the results measured after the positive electrode sheet is cleaned. The reason is that the dissolved manganese and electrolyte attached to the surface of the positive electrode material are not removed. This part of the manganese dissolved due to the circulation enters the second solution to be tested, the manganese content in the second solution to be tested increases, and the manganese dissolution result is low.
[0155] Comparison of the data results of Example 1 and Comparative Example 2, Example 3 and Comparative Example 4, and Example 5 and Comparative Example 6 shows that the manganese dissolution is calculated by directly measuring the manganese content in the negative electrode, and the result is quite different from the manganese dissolution amount obtained by comparing the manganese content before and after the positive electrode material cycle. This is because the dissolved manganese on the surface of the positive electrode material and the dissolved manganese in the electrolyte are not calculated, and there is a certain error in calculating the amount of active components. The change in the manganese dissolution amount before and after the positive electrode material cycle in the positive electrode sheet is tested as the manganese dissolution value with higher accuracy.
[0156] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for testing the dissolution of manganese in a battery, characterized in that: The test method comprises the following steps: (1) Take the battery before and after the cycle, disassemble them respectively to prepare the test solution, which specifically includes the following steps: (a) disassembling the battery to obtain a positive electrode sheet, placing the positive electrode sheet in a detergent for ultrasonic treatment, and then drying and scraping the positive electrode material off the surface of the current collector to obtain a positive electrode material, wherein the positive electrode material includes an active component; The ultrasonic process is accompanied by heating; (b) digesting the cathode material, and diluting the digestion solution to obtain a solution to be tested; Wherein, when the battery is a battery before cycling, the prepared solution to be tested is the first solution to be tested; when the battery is a battery after cycling, the prepared solution to be tested is the second solution to be tested; (2) The manganese content in the first test solution is recorded as a, the manganese content in the second test solution is recorded as b, and the manganese dissolution amount in the battery is recorded as ((ab) / a)×100%.
2. The testing method according to claim 1, characterized in that: The detergent used for cleaning in step (1) is one of water, anhydrous ethanol and ethanol-water solution.
3. The testing method according to claim 2, characterized in that: The volume concentration of ethanol in the ethanol aqueous solution is 40%-75%.
4. The testing method according to claim 1, characterized in that: The frequency of the ultrasound is 20KHz-40KHz, and the number of ultrasounds is 1 time-3 times.
5. The testing method according to claim 1, characterized in that: The heating temperature is 40°C-60°C.
6. The testing method according to claim 1, characterized in that: The washing time is 8 min-12 min.
7. The testing method according to claim 1, characterized in that: The drying temperature is 80°C-130°C.
8. The testing method according to claim 1, characterized in that: The drying time is 5h-10h.
9. The testing method according to claim 1, characterized in that: The digestion in step (b) includes at least one of wet digestion, dry digestion and microwave digestion.
10. The testing method according to claim 9, characterized in that: The digestion in step (b) is wet digestion.
11. The testing method according to claim 9, characterized in that: The digestion agent in the wet digestion is an acidic compound, including at least one of hydrochloric acid, nitric acid, perchloric acid and aqua regia.
12. The testing method according to claim 11, characterized in that: The digestion agent in the wet digestion is nitric acid and / or hydrochloric acid.
13. The testing method according to claim 1, characterized in that: The digestion agent concentration in step (b) is 0.1 mol / L-10 mol / L.
14. The testing method according to claim 13, characterized in that: The digestion agent concentration in step (b) is 0.4 mol / L-1 mol / L.
15. The testing method according to claim 1, characterized in that: The amount of the digestion agent used in the digestion of step (b) is 20mL / 1g-50mL / 1g of positive electrode material.
16. The testing method according to claim 1, characterized in that: The digestion time in step (b) is 20 min-40 min.
17. The testing method according to claim 1, characterized in that: The digestion temperature in step (b) is 60°C-300°C.
18. The testing method according to claim 17, characterized in that: The digestion temperature in step (b) is 80°C-120°C.
19. The testing method according to claim 1, characterized in that: The method for diluting and fixing the volume of the digestion solution in step (b) is: transferring the digestion solution to a volumetric flask with a volume of V, adding water to fix the volume, then taking out a solution with a volume of V0 from the volumetric flask and transferring it to another volumetric flask with a volume of V, adding acid, and then fixing the volume with water to obtain a solution to be tested.
20. The testing method according to claim 19, characterized in that: The volume ratio of the solution with a volume of V0 to the acid is 1:(8-12).
21. The testing method according to claim 1, characterized in that: The acid used for dilution and volume determination in step (b) comprises at least one of hydrochloric acid, nitric acid, perchloric acid and aqua regia.
22. The testing method according to claim 1, characterized in that: Step (1) The positive electrode sheet includes a manganese-containing positive electrode active component, and the manganese-containing positive electrode active component includes LiMn x Fe 1-x PO4,0<x≤1.
23. The testing method according to claim 1, characterized in that: The current collector includes at least one of aluminum foil and nickel foil.
24. The testing method according to claim 23, characterized in that: The current collector is aluminum foil.
25. The testing method according to claim 1, characterized in that: Step (3) The test methods for the content of manganese in the first test solution and the second test solution independently include at least one of ICP-OES, ICP-AES and ICP-MS.
26. The testing method according to claim 1, characterized in that: The test method comprises the following steps: (1) Take the battery before and after the cycle, disassemble them respectively to prepare the test solution, which specifically includes the following steps: (a) disassembling the battery to obtain the positive electrode sheet, placing the positive electrode sheet in a detergent and ultrasonicating at 40°C-60°C for 8min-12min, for a total of 1-3 times, with a frequency of 20KHz-40KHz, and replacing the detergent every time the ultrasonication is performed, and then drying at 80°C-130°C for 5h-10h, and after drying, scraping the positive electrode material from the surface of the current collector to obtain the positive electrode material; (b) The positive electrode material is placed in an acidic compound of 0.1 mol / L-10 mol / L for digestion. The amount of the digester is 20 mL / 1 g-50 mL / 1 g of the positive electrode material. The digestion temperature is 60°C-300°C. The digestion time is 20 min-40 min. The filtrate is separated from the solid and liquid and used as the digestion solution. The digestion solution is then diluted twice to obtain a fixed volume to obtain a test solution. Wherein, when the battery is a battery before cycling, the prepared solution to be tested is the first solution to be tested; when the battery is a battery after cycling, the prepared solution to be tested is the second solution to be tested; (2) The manganese content in the first test solution is recorded as a, the manganese content in the second test solution is recorded as b, and the manganese dissolution amount in the battery is recorded as ((ab) / a)×100%.
27. Application of the test method for manganese dissolution in batteries according to any one of claims 1 to 26 in the field of lithium-ion batteries.
Citation Information
Patent Citations
Precursor and LMFP and preparation method and application thereof
CN105514422A
Method for measuring conversion rate of trivalent nickel in cathode material of nickel-metal hydride accumulator
CN101936913A